The impact of the global financial crisis on emerging financial markets - Batten, Jonathan; Szilagyi, Peter G., 1976- (Emerald, 2011)
The Global Financial Crisis of 2007-2009 has highlighted the resilience of the financial markets and broader economies from the developing world. This outcome owes much to the bitter experience and economic strategies developed and implemented at both a national and international level following the Asian Financial Crisis of 1997-1998. The objective of this volume is to investigate and assess the impact and response to the crisis from an emerging markets perspective including asset pricing, contagion, financial intermediation, market structure and regulation. Our hope is that the assembled papers will offer clear insights into the complex financial arrangements that now link emerging and developed financial markets in the current economic environment. The volume spans four dimensions: first, a series of background studies offer explanations of the causes and impacts of the crisis on emerging markets more generally; then, implications are considered. The third and final sections provide insights from regional and country-specific perspectives.
Keywords: Global Financial Crisis, 2008-2009.; elektronické knihy; electronic books